2021
DOI: 10.1080/02568543.2021.1960937
|View full text |Cite
|
Sign up to set email alerts
|

Mindful Acceptance Predicts Writing Achievement in 6th-Graders

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 83 publications
0
4
0
Order By: Relevance
“…Given the longitudinal nature of the study, this result suggests that past performance in transcription and executive functions does not predict later text quality. Despite contradicting the theoretical prepositions about the role of transcription and executive functions in writing, these findings join to a set of empirical research raising questions about the predictive nature of these relationships, typically stemming from cross‐sectional studies (e.g., Cordeiro et al, 2021; Kim & Schatschneider, 2017). Abbott et al (2010) also found few longitudinal relationships between handwriting and written composition, and Graham and Santangelo (2014) showed that spelling instruction had no impact on measures of writing performance.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Given the longitudinal nature of the study, this result suggests that past performance in transcription and executive functions does not predict later text quality. Despite contradicting the theoretical prepositions about the role of transcription and executive functions in writing, these findings join to a set of empirical research raising questions about the predictive nature of these relationships, typically stemming from cross‐sectional studies (e.g., Cordeiro et al, 2021; Kim & Schatschneider, 2017). Abbott et al (2010) also found few longitudinal relationships between handwriting and written composition, and Graham and Santangelo (2014) showed that spelling instruction had no impact on measures of writing performance.…”
Section: Discussionmentioning
confidence: 81%
“…Similarly, among third, fourth and fifth graders, Altemeier et al (2008) found that inhibitory control and cognitive flexibility contributed to spelling and written expression. Nevertheless, in recent studies with primary and middle graders, both inhibitory control and cognitive flexibility failed to predict text quality (Cordeiro et al, 2019, 2021). Moreover, when considering latent factors to represent executive functions in a sample of Grade 1 children followed into Grade 2, Hooper et al (2011) showed that executive functions had a stable contribution to spelling and written expression across grades.…”
Section: Introductionmentioning
confidence: 96%
“…Another study found that a meditationbased intervention led to attentional improvements and better grades in Portuguese, Mathematics and Social Studies (Magalhães et al, 2022). Cordeiro et al (2021) found that students' ability to approach their own thoughts and feelings with an acceptance orientation (i.e., mindful acceptance) predicted their writing achievement in Grade 6. Rocha et al (2023) combined SRSD interventions with a meditation component and found that meditation was essential for 3rd grade students, especially for those with poor results on writing performance at pretest which achieved better academic performance in posttest; also, the intervention showed general improvements in planning skills, complexity of the texts and better executive functioning.…”
Section: Introductionmentioning
confidence: 94%
“…Yet, the importance of attentional skills has already been highlighted in writing models such as the WWC (Graham, 2018) and the Not-So-Simple View of Writing (Berninger and Winn, 2006). Moreover, there is some empirical evidence suggesting that attention contributes to writing achievement in early school years (Cordeiro et al, 2021). The question raised by these evidence is how to improve children's attention in order to boost their writing performance?…”
Section: Introductionmentioning
confidence: 99%